2020
DOI: 10.1111/jam.14873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different glucogenic to lipogenic nutrient ratios on rumen fermentation and bacterial community in vitro

Abstract: Aims: This study was to investigate the effect of different ratios of glucogenic to lipogenic nutrients on rumen fermentation and the corresponding ruminal bacterial communities. Methods and Results: Four diets, including glucogenic diet (G), lipogenic diet (L), two mixed diets: GL1 (G: L = 2 : 1) and GL2 (G:L = 1 : 2), served as substrates and were incubated with rumen fluid in vitro. The results revealed that the gas production, dry matter digestibility and propionate proportion were significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Ruminobacter , an amylolyic bacterium able to degrade proteins, was also found at a higher level in the rumen with dietary supplementation with A. nodosum or L. digitata [ 67 ]. A previous study showed that DMD and gas production were positively correlated with Ruminobacter [ 68 ], which was confirmed by the rumen fermentation data of this study. The relative abundance of Fibrobacter , another main cellulose-degrading bacterium in the rumen [ 69 ], was also significantly increased by the addition of PT.…”
Section: Discussionsupporting
confidence: 90%
“…Ruminobacter , an amylolyic bacterium able to degrade proteins, was also found at a higher level in the rumen with dietary supplementation with A. nodosum or L. digitata [ 67 ]. A previous study showed that DMD and gas production were positively correlated with Ruminobacter [ 68 ], which was confirmed by the rumen fermentation data of this study. The relative abundance of Fibrobacter , another main cellulose-degrading bacterium in the rumen [ 69 ], was also significantly increased by the addition of PT.…”
Section: Discussionsupporting
confidence: 90%
“…NH 3 -N concentrations are associated with the rate of nitrogen use by rumen microorganisms. Some functional rumen bacteria, such as Prevotella and Quinella , can improve the digestibility of dietary protein and metabolism of amino acids, resulting in the production of high concentrations of NH 3 -N ( 65 , 66 ). This result is consistent with the greater abundance of Prevotella and the higher concentrations of NH 3 -N in the Tibetan sheep of the OHF group.…”
Section: Discussionmentioning
confidence: 99%
“…The principal coordinates analysis (PCoA) was analyzed with the method of unweighted UniFrac distance to compare the interrelationships of bacterial communities between diets using the R software (3.4.4). The community richness and diversity were analyzed by the alpha diversity indexes including the OTU, Chao 1, ACE, Shannon, and Simpson (Hua et al, 2021).…”
Section: Illumina Miseq Sequencing and Analysismentioning
confidence: 99%